ANALISIS LAPORAN ARUS KAS DALAM MENILAI KINERJA KEUANGAN PADA PT BUMI SERPONG DAMAI TBK TAHUN 2021-2023 - HANDAYANI, R. SRI; NURFITRIANI, NURFITRIANI; HUDA, MUHAMMAD MIFTAKHUL (Fakultas Ekonomi Universitas Islam Indragiri, 2024)
The objective of the research conducted is to assess the financial performance of PT. Bumi Serpong Damai, Tbk based on the analysis of cash flow ratios for the years 2021-2023. The tools used for analysis are the cash flow ratios, which consist of the operating cash flow ratio, the cash coverage ratio against interest, the capital expenditure ratio, the operating cash flow ratio against total debt, and the cash coverage ratio against net income.. The research method used is a quantitative descriptive method. The results of the study show that the operating cash flow ratio and the operating cash flow ratio against total debt have performed poorly in meeting the company's obligations during the years 2021-2023. The cash coverage ratio against interest and the capital expenditure cash flow ratio show good results during the years 2021-2023, indicating that the company has sufficient cash flow to cover interest expenses and taxes and to repay the principal debt. Meanwhile, the cash coverage ratio against net income shows good results in 2021-2022, where net income is supported by a larger operating cash flow, indicating good earnings quality; however, in 2023, it shows a poorer result